2016
DOI: 10.1007/s41042-016-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Interventions and Chronic Non-Cancer Pain: A Systematic Review of the Literature

Abstract: Chronic pain is a multi-faceted, pervasive condition associated with significant psychosocial impairment. Positive psychological interventions (PPIs) are increasingly delivered in clinical settings, with recent research offering evidence supporting the application of PPIs in predominantly mental-health contexts. To date, no review has considered the impact of PPIs applied in physical-health settings. The aim of this systematic review is to collate the available evidence and identify psychosocial factors that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…21 Hope-based interventions have been shown to significantly increase levels of well-being. 22,23 Personal goals are also thought to promote hope. Specifically, goal-focused hope is defined as future oriented goal motivation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…21 Hope-based interventions have been shown to significantly increase levels of well-being. 22,23 Personal goals are also thought to promote hope. Specifically, goal-focused hope is defined as future oriented goal motivation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“… Weighted kappa was 0.70 (substantial agreement) QATSDD does not provide cut-off points for quality rating of individual studies as good, fair or poor. Iddon J.E [ 55 ]. 2016 UK Psychology A systematic review investigating positive psychological interventions and chronic non-cancer pain.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis revealed a number of perceived areas of strength of the tool including its strong reliability and validity [ 33 , 55 , 66 ]. All of the reviews within the 39 included articles that used the tool confirmed its reliability and validity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto al primer punto, en el campo del dolor, el cambio de enfoque hacia el desarrollo de programas de tratamiento que promuevan factores positivos se hace evidente en los resultados de una reciente revisión sistemática de intervenciones psicológicas positivas en síndromes de dolor crónico (Iddon, Dickson y Unwin, 2016). En este trabajo se analizan 8 estudios (2 estudios cualitativos y 6 estudios cuantitativos) de los cuales todos excepto uno se desarrollaron a partir del año 2014.…”
Section: Nuevos Abordajes Terapéuticos Para El Tratamiento De La Fibrunclassified